2020
DOI: 10.2147/cmar.s221731
|View full text |Cite
|
Sign up to set email alerts
|

<p>Up-Regulation of MicroRNA-21 Indicates Poor Prognosis and Promotes Cell Proliferation in Esophageal Squamous Cell Carcinoma via Upregulation of lncRNA SNHG1</p>

Abstract: Introduction: MicroRNA-21 (miRNA-21) and lncRNA SNHG1 (small nucleolar RNA host gene 1) are known to be aberrantly upregulated and promote tumor progression in various cancers. Nevertheless, very few studies have determined the roles of tissue and circulating miRNA-21 and SNHG1 in ESCC patients. Particularly, knowledge about the characteristics of miRNA-21 and SNHG1 expression and their correlations with survival rates, as well as their interaction with each other remains inadequate in ESCC. Methods: Thse expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…It was shown that serum exosomal miR-320d is a promising noninvasive diagnostic biomarker for distinguishing metastatic from nonmetastatic colorectal cancer [34]. miRNA-21 and lncRNA SNHG1 (small nucleolar RNA host gene 1) may serve as potential diagnostic, prognostic biomarkers and therapeutic targets for esophageal squamous cell carcinoma patients [35]. Exosomal microRNAs have a key role in the tumor microenvironment of breast cancer and may serve as molecular markers [36].…”
Section: Composition Of Cancer Exosomesmentioning
confidence: 99%
“…It was shown that serum exosomal miR-320d is a promising noninvasive diagnostic biomarker for distinguishing metastatic from nonmetastatic colorectal cancer [34]. miRNA-21 and lncRNA SNHG1 (small nucleolar RNA host gene 1) may serve as potential diagnostic, prognostic biomarkers and therapeutic targets for esophageal squamous cell carcinoma patients [35]. Exosomal microRNAs have a key role in the tumor microenvironment of breast cancer and may serve as molecular markers [36].…”
Section: Composition Of Cancer Exosomesmentioning
confidence: 99%
“…Also, the expression level of circulating exosomal miR-25-3p is also associated with the metastasis of colorectal cancer [ 21 ]. In addition, exosomal miRNAs are also significant in other types of tumors, such as esophageal squamous cell carcinoma [ 22 ] and breast cancer [ 15 ], and serve as molecular biomarkers [ 23 ].…”
Section: Formation and Contents Of Cancer Exosomesmentioning
confidence: 99%
“…miRNA-21 is upregulated in different types of tumors, such as esophageal squamous cell carcinoma and breast, lung and liver cancer, and targets tumor-suppressive mRNAs (49,50). It was demonstrated that overexpression of serum ex-miRNA-21 was diagnostic of pancreatic ductal adenocarcinoma (51).…”
Section: Discussionmentioning
confidence: 99%